2020
DOI: 10.3389/fdgth.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Scores in Alzheimer's Disease: Current Applications and Future Directions

Abstract: Genome-wide association studies have identified nearly 40 genome-wide significant single nucleotide polymorphisms (SNPs) which are associated with Alzheimer's Disease (AD). Due to the polygenicity of AD, polygenic risk scores (PRS) have shown high potential for AD risk prediction. PRSs have been shown to successfully discriminate between AD cases and controls achieving a prediction accuracy of up to 84% based on area under the receiver operating curve. The prediction accuracy in AD is higher compared with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 36 publications
0
54
0
Order By: Relevance
“…No associations were found between AD PRS or CAD PRS and baseline total WBV and WMH volumes across all diagnostic groups, although PRSs have been shown to be predictive of AD risk 40 . That said, AD PRS beyond APOE is correlated with white matter load in the occipital lobe in AD subjects upon the inclusion of many variants (polygenic p=0.5).…”
Section: Discussion [1771 Words]mentioning
confidence: 71%
“…No associations were found between AD PRS or CAD PRS and baseline total WBV and WMH volumes across all diagnostic groups, although PRSs have been shown to be predictive of AD risk 40 . That said, AD PRS beyond APOE is correlated with white matter load in the occipital lobe in AD subjects upon the inclusion of many variants (polygenic p=0.5).…”
Section: Discussion [1771 Words]mentioning
confidence: 71%
“…This has directed the focus on investigating other pathways and other possible genetic variants associated with AD. Genome Wide Association Studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) that are associated with an increased risk of developing AD in late life ( Baker and Escott-Price, 2020 ). These include CLU, PICALM, and CR1 as well as BIN1, ABCA7, and EPHA1 ( Harrison and Bookheimer, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of predictive modeling implies further practical applications in the field of clinical assessment [ 25 ]. For example, recent attempts showed a promising advancement of using predictive pattern scores of dementia in the multidimensional dataset, such as genetic polymorphisms or brain structural imaging [ 61, 62 ]. Likewise, translation from cognitive task performance to real-world functioning requires complex translation.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the two linear models, the combination of multiple subtests of the neuropsychological battery in a linear fashion showed a marginal increase in predictive accuracy, indicating that the current The use of predictive modeling implies further practical applications in the field of clinical assessment [25]. For example, recent attempts showed a promising advancement of using predictive pattern scores of dementia in the multidimensional dataset, such as genetic polymorphisms or brain structural imaging [61,62]. Likewise, translation from cognitive task performance to real-world functioning requires complex translation.…”
mentioning
confidence: 99%